2016
DOI: 10.1515/cclm-2016-0271
|View full text |Cite
|
Sign up to set email alerts
|

Transcript expression and genetic variability analysis of caspases in breast carcinomas suggests CASP9 as the most interesting target

Abstract: Genetic variability in CASP9 and expression of its splicing variants present targets for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…27 In this study, the expression of CASP9 showed a significant decrease, although OXR1 was suppressed in ESCC. The decreased mRNA levels of CASP9 were found in different cancer cells, such as hepatocellular carcinoma, breast carcinomas, and colorectal cancer, [28][29][30] whereas the up-regulation of CASP9 was observed when the proliferation of tumors was inhibited. Some studies have reported that CASP9 can be down-regulated by multiple miRNAs in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…27 In this study, the expression of CASP9 showed a significant decrease, although OXR1 was suppressed in ESCC. The decreased mRNA levels of CASP9 were found in different cancer cells, such as hepatocellular carcinoma, breast carcinomas, and colorectal cancer, [28][29][30] whereas the up-regulation of CASP9 was observed when the proliferation of tumors was inhibited. Some studies have reported that CASP9 can be down-regulated by multiple miRNAs in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Caspases (cysteine-dependent aspartyl-specific protease) belong to a family of cysteine proteases that cleave target proteins at specific aspartate residues (Alnemri et al, 1996;Nicholson et al, 1995;Julien et al, 2016) and mediate proteolytic events indispensable for biological phenomena such as inflammation cell death or apoptosis (Sadowski-Debbing et al, 2002;Brynychova et al, 2016;Larsen & Sorensen 2017). It is now clear that caspases are thought to play a pivotal role in apoptosis as an evolutionarily conserved function (Seidelin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%